Cerebrospinal Fluid Concentration of Key Autophagy Protein Lamp2 Changes Little During Normal Aging - Loeffler, David A.; Klaver, Andrea C.; Coffey, Mary P.; Aasly, Jan O. (Frontiers in Aging Neuroscience, 2018)
Autophagy removes both functional and damaged intracellular macromolecules from cells via lysosomal degradation. Three autophagic mechanisms, namely macroautophagy, chaperone-mediated autophagy (CMA), and microautophagy, have been described in mammals. Studies in experimental systems have found macroautophagy and CMA to decrease with normal aging, despite the fact that oxidative stress, which can activate both processes, increases with normal aging. Whether autophagic mechanisms decrease in the human brain during normal aging is unclear. The primary objective of this study was to examine the association of a major autophagy protein, lysosome-associated membrane glycoprotein (lamp2), with age in cerebrospinal fluid (CSF) samples from healthy subjects. Lamp2 consists of three isoforms, lamp2a, 2b and 2c, all of which participate in autophagy. Lamp2’s CSF concentration decreases in Parkinson’s disease (PD) and increases in Alzheimer’s disease (AD), but whether its CSF concentration changes during normal aging has not been investigated. Our secondary objectives were to examine the associations of lamp2’s CSF concentration with CSF levels of the molecular chaperone heat shock 70-kDa protein (HSPA8), which interacts with lamp2a in CMA, and oxidative stress markers 8-hydroxy-2′-deoxyguanosine (8-OHdG), 8-isoprostane (8-ISO) and Total Antioxidant Capacity (TAC) in healthy subjects. We found lamp2’s observed associations with these variables to be weak, with all Kendall’s tau-b absolute values ≤0.20. These results suggest that CSF lamp2 concentration changes little during normal aging and does not appear to be associated with HSPA8 or oxidative stress. Further studies are indicated to determine the relationship between CSF lamp2 concentration and brain autophagic processes.